Root system distribution of sugarcane irrigated with domestic sewage effluent aplication by subsurface drip system - Allan C. M. de Sousa; Edson E. Matsura; Marcelo L. C. Elaiuy; Leonardo N. S. dos Santos; Célia R. Montes; Regina C. de M. Pires (Engenharia Agrícola, 2013)
Irrigation with domestic sewage effluent (DSE) has been recommended by subsurface dripping, as it can obtain a high rate of irrigation efficiency and faster use of salts in comparison with other irrigation methods. The study aimed at evaluating the area, the length and the effective depth of the root system of sugarcane irrigated with DSE by subsurface drip system and with different irrigation rates at depths of 0.00-0.20, 0.20-0.40, 0.40-0.60 and 0.60-0.80m. The experiment was carried out in the municipality of Piracicaba, in the state of São Paulo (SP), Brazil, in a sugarcane area irrigated with DSE in a completely randomized blocks set up in furrows, with three replications and four treatments, which are: one area without irrigation (AWI) and three irrigated areas meeting 50% (T50%), 100% (T100%) and 200% (T200%) of the crop's water need between each round of irrigation. T100% and T200% provided smaller areas and lengths of roots in the two deepest layers, as compared to AWI and T50%, which stimulated the development of deeper roots due to the water stress. TWI, T100% and T200% presented 80% of the roots up to a depth of 0.40m and T50% treatment presented 76.43% of roots total.